Химия учебное пособие - Денисов В. В. Владимир Викторович; Дрововозова Т. И. Татьяна Ильинична; Лозановская И. Н. Ирина Николаевна; Луганская И. А. Ирина Анатольевна; Хорунжий Б. И. Борис Иванович (Учебный курс)
Соответствует государственному стандарту по дисциплине "Химия"